2016
DOI: 10.1259/bjr.20150956
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion in non-occlusive mesenteric ischaemia (NOMI): effectiveness of CT in an emergency setting

Abstract: Objective: To investigate the CT features of reperfusion (presence/absence) in non-occlusive mesenteric ischaemia (NOMI) and their prognostic value in an emergency setting. Methods: A revision was undertaken of imaging from 20 patients (16 males/4 females) with a dismissal summary of NOMI. All patients had previously undergone a minimum of one multidetector CT examination, and consequently underwent surgery (n 5 8), autopsy (n 5 2), angiography (n 5 1) or endoscopy (n 5 9). An evaluation of the CT scans was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Other secondary signs—examined separately—were deemed insufficient for diagnosing NOMI in MSCT. Other reports suggest that they could offer greater confidence in the diagnosis [ 24 , 27 , 28 ] of NOMI, but in the authors’ opinion cannot be regarded as a single specific indicator. A definite, but small (R1 = 0.31; R2 = 0.29) and not significant (R1 p = 0.10; R2 p = 0.12) correlation was found for reduced contrast enhancement of the bowel wall, as the best of the secondary signs.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Other secondary signs—examined separately—were deemed insufficient for diagnosing NOMI in MSCT. Other reports suggest that they could offer greater confidence in the diagnosis [ 24 , 27 , 28 ] of NOMI, but in the authors’ opinion cannot be regarded as a single specific indicator. A definite, but small (R1 = 0.31; R2 = 0.29) and not significant (R1 p = 0.10; R2 p = 0.12) correlation was found for reduced contrast enhancement of the bowel wall, as the best of the secondary signs.…”
Section: Discussionmentioning
confidence: 88%
“…Additionaly, as postulated by Mazzei et al, CT could reveal the different appearances of NOMI upon imaging depending on the time at which the CT examination is performed and thus, on presence or absence of reperfusion. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…NOMI is very rare clinical condition, but it has a very high mortality rate of 30–68.5% even now [ [4] , [5] , [6] , [7] ]. The pathogenesis of NOMI is vasospasm of mesenteric arteries, and the blood flow is not completely interrupted in contrast to superior mesenteric artery occlusion [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-occlusive mesenteric ischemia (NOMI) accounts for 20-30 % of all acute mesenteric ischemia [1], and has a high mortality rate (50-83 %) [2]. NOMI is a form of acute mesenteric ischemia that is caused by splanchnic hypoperfusion without digestive vascular occlusion [1], reflecting intense splanchnic vasoconstriction [3,4], commonly caused by shock, hemorrhage, surgery, dialysis, hypovolemia, cardiogenic injuries, vasoactive treatments, or intoxication [5]. The diagnosis of NOMI remains challenging, and previous studies have indicated that the diameter of the superior mesenteric artery could be of help in the diagnosis [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of NOMI remains challenging, and previous studies have indicated that the diameter of the superior mesenteric artery could be of help in the diagnosis [6,7]. However, the diagnosis of NOMI relies mainly on evidence of bowel injury, which may be difficult to interpret in case of reperfusion [4,6,9]. Beyond the diagnosis of NOMI, the prognosis of patients suffering for NOMI prognosis is poor, and is not well understood, depending on various factors, such as disease severity, sepsis, shock and multiple organ failure.…”
Section: Introductionmentioning
confidence: 99%